Development of Nanosuspension of Artemisia absinthium Extract as Novel Drug Delivery System to Enhance Its Bioavailability and Hepatoprotective Potential - Nazish Jahan; Fareeha Kousar; Khalil Ur Rahman; Syeeda Iram Touqeer; Naseem Abbas (Journal of Functional Biomaterials, 2023)
A nanosuspension of Artemisia absinthium extract was formulated and characterized for the enhancement of bioavailability and better hepatoprotective efficacy. The nanosuspension of A. absinthium extract was formulated using an antisolvent precipitation technique, and various formulation parameters were optimized using response surface methodology (RSM). The optimized nanosuspension was characterized using AFM and FT–IR spectroscopy. The drug-release profile and oral bioavailability of the optimized nanosuspension were assessed with reference to coarse suspension. The DPPH radical scavenging method was used to measure the nanosuspension’s antioxidant activity, and its in vivo hepatoprotective potential was assessed against CCl4-induced hepatic injury in rats. The developed optimized nanosuspension had suitable zeta potential of −11.9 mV, PDI of 0.285, and mean particle size of 253.8 nm. AFM study demonstrated a homogeneous population of nanoparticles with average size of 25 nm. The formulated nanosuspension of A. absinthium showed faster dissolution rate and 1.13-fold enhanced bioavailability as compared to the coarse suspension (plant extract). Furthermore, the nanoformulation had stronger antioxidant and hepatoprotective potential as compared to the unprocessed coarse extract. These results demonstrated that nanosuspension is a promising strategy for improving the oral bioavailability and bioactivities of A. absinthium extract.